PHPU 3. Nutritional evaluation of selected Philippine traditional maize as an alternative source for rice-corn blends (2018)
The Department of Agriculture (DA) and the National Food Authority (NA) launched the Bigas-Mais Blend last 2017. Currently, the Institute of Plant Breeding (IPB) is promoting rice-corn blend using IPB Var 6, a Quality Protein Maize (QPM). However, just like rice, the search for alternative maize varieties is also needed as the demand increases. Traditional varieties are genetically diverse and are mostly found in areas, where corn is used as staple. Thus, IPB started to collect and characterize traditional maize from all over the Philippines. Six traditional maize accessions were identified by previous studies to be downy mildew resistant (CGUARD DM1), high in antioxidants (CGUARD N126, CGUARD N68 and CGUARD N15), high in protein and lysine (CGUARD N2) and high in starch (CGUARD N37). These accessions were processed into grits and different rice-corn blends (70:30, 50:50 and 30:70) were cooked. Proximate composition, minerals content, percent scavenging activity and glycemic index (GI) were evaluated. At a=0.05, the blends showed variability on their nutritional composition. In general, 30:70 rice-corn blend was identified to be the best blend in terms of nutritional quality. The 30:70 blend of CGUARD N2 had the highest crude protein (9.90%) while the 30:70 blend of CGUARD N27 had the highest crude fiber (3.95%). The 30:70 blend of CGUARD N126 gave the highest scavenging activity (34.68%). On the other hand, the 50:50 blend of CGUARD N2 had the highest iron content (1.86 mg/100 g) while the 70:30 blend of CGUARD N68 had the highest zinc content (1.74 mg/100 g). It was also observed that the Gl of all blends are much lower compared to pure rice. The lowest GI (58.45) was observed on 30:70 blend of CGUARD N37. Considering the nutritional quality of traditional maize, it can be a good alternative source of rice-corn blends. However, sensory evaluations are needed to determine the eating quality of these accessions.